Analisis Yuridis terhadap Kerugian Reputasional sebagai Dasar Gugatan Perdata di Luar Hubungan Kontraktual dalam Kerangka Perbuatan Melawan Hukum Menurut KUHPerdata - Raffi Rizkytia Novebryan; Wahyuningrum W; Siti Ahdia Fawwaz Nurwendha; Nandar Wulan; Raul Gindo Cahayo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Reputational damage constitutes a form of non-material loss that has gained increasing relevance in the development of civil law, particularly in the context of claims arising outside contractual relationships. In practice, reputational damage often results from unlawful acts, such as defamation, dissemination of false information, or other actions that harm an individual’s honor and good name. The issue that arises concerns the legal standing of reputational damage as a basis for civil claims and the legal framework for assessing and awarding compensation for such losses. This study aims to analyze reputational damage as a basis for civil litigation outside contractual relationships within the framework of unlawful acts under the Indonesian Civil Code. The research employs a normative juridical method with statutory and conceptual approaches, through the examination of legal norms, doctrines, and relevant academic literature. The findings indicate that reputational damage can be classified as a form of immaterial loss arising from unlawful acts as stipulated in Article 1365 of the Civil Code. However, proving reputational damage remains challenging due to its abstract nature and the difficulty in quantifying it.